2018
DOI: 10.3390/nu10040526
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin Is a Lipid-Induced Gastrointestinal Peptide Associated with Visceral Adipose Tissue Inflammation in Obesity

Abstract: Neurotensin (NT) is a 13-amino acid peptide localized in the neuroendocrine cells of the small intestine, which promotes fat absorption and fatty acids translocation in response to lipid ingestion. NT-knock-out mice fed with a high-fat diet are protected from obesity, fatty liver, and the development of insulin-resistance. In humans, higher plasma levels of pro-NT, which is the stable circulating precursor of NT, predict obesity, type 2 diabetes (T2D), and cardiovascular disease. In obesity, the presence of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 25 publications
9
46
1
1
Order By: Relevance
“…For the other genes identified, there was no direct evidence in the literature for a direct role in cholesterol metabolism, although some interesting patterns were evident. For example, we observed multiple genes involved in immunoglobulin production ( IGLC5, IGLC6 and IGLV4-69 ) and insulin metabolism ( UNC5B, DEPP1 ), observations at least consistent with the role of cholesterol in inflammation and insulin resistance 36,37 . Of note, for all 15 genes, the effect direction estimated by MR-link was concordant with the direction estimated by other MR-methods ( Table 1, Table 2, Supplemental Figure 3 and Supplemental Table 6 ).…”
Section: Resultssupporting
confidence: 73%
“…For the other genes identified, there was no direct evidence in the literature for a direct role in cholesterol metabolism, although some interesting patterns were evident. For example, we observed multiple genes involved in immunoglobulin production ( IGLC5, IGLC6 and IGLV4-69 ) and insulin metabolism ( UNC5B, DEPP1 ), observations at least consistent with the role of cholesterol in inflammation and insulin resistance 36,37 . Of note, for all 15 genes, the effect direction estimated by MR-link was concordant with the direction estimated by other MR-methods ( Table 1, Table 2, Supplemental Figure 3 and Supplemental Table 6 ).…”
Section: Resultssupporting
confidence: 73%
“…Previously, serum pro-NT levels have been reported to be notably increased in several metabolic diseases such as obesity [19], type 2 diabetes mellitus [20,21], and nonalcoholic fatty liver disease (NAFLD) [22]. Our present results first found that serum pro-NT levels were significantly higher in patients with premature CAD (males <55 years and females <65 years), especially for patients with BMI<25 kg/m 2 , and premature CAD was an independent contributor to serum pro-NT levels after adjusting for some confounders.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the absolute majority of the NT that is measurable in blood comes from the periphery, i.e. from the small intestine, where it is stimulated by dietary fat intake [6].…”
Section: Introductionmentioning
confidence: 99%